Parasites of Sika deer in the Land of the Leopard National Park and neighboring territories - D. N. Kuznetsov; D. A. Maksimova; A. S. Moskvin; N. V. Esaulova (Российский паразитологический журнал)
The purpose of the research is to obtain information on the taxonomic composition of parasites of Sika deer (Cervus nippon) living in the Land of the Leopard National Park and neighboring territories.Materials and methods. Thirteen Sika deer that died from various causes in the Land of the Leopard National Park and neighboring territories (the southwest of Primorsky Krai, Russian Far East) from December 2021 to April 2024 were examined. The taxonomic affiliation of detected parasites was determined by morphological peculiarities.Results and discussion. All the Sika deer examined were found to have nematodes, with trichostrongylids of the species Spiculopteragia asymmetrica predominating. Single specimens of the spirurids Pygarginema skrjabini were also found in four animals. The trichostrongylids Ashworthius sidemi were found in two deer. In addition, a trematode from the Paramphistomidae family was recorded. The deer keds Lipoptena cervi were also found on one of the deer.